Mangosteen Rind towards Mechanical Trauma Recovery in the Oral Cavity (in vivo) - Lanny Sunarjo; Ratnawati Hendari; Nono Sulistijarso (Jurnal Riset Kesehatan, 2014)
Aim of this study was to determine the effect of the application of paste of mangosteen rind to measure the diameter of ulcers due to scratches (mechanical trauma). This type of research is experimental (in vivo), the research design of the pre-post test control group design. The population is Male Wistar rats using a completely randomized block sampling, there are 2 (two) groups, respectively 6 (six) tails, the total animal is 12, where 1 (one) treatment group were oiled paste mangosteen rind and another group was smeared PVP. The results showed there is effect of the application of paste of mangosteen rind towards mechanical trauma recovery, diameter of the ulcer which gradually shrinking on day 3, 7th and ulcers experience healing on day 10. Need further research on the effect of the application of paste of mangosteen rind against oral mucosal ulcer healing pathologically.